EVALUASI DESAIN OPERASI PELAYANAN PERBANKAN - Hesti Maheswari; Yuga Rawikara (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
This thesis discusses the Customer ratings for services provided and determine the factors that are considered essential services by customers, but not both in its implementation. The data obtained by conducting direct observation by distributing questionnaires to the Customer SRB Majesty Eternal Blessings and through direct interviews to the company to get the data: Technical characteristic and direction of development is used to obtain the data directly from the company The sampling technique used was convenience sampling, whereas analytical tool used is the analysis of the Quality Function Deployment (QFD), Validity and reliability of test data. From the test results showed twenty-eight attributes are distributed through the questionnaire questions, the importance and validity test of consumer satisfaction, twenty-eight of the attributes of all the items declared invalid and the test analysis HOQ reliabel.dan there needs to be redesigned because it is not accordance with the expectations of the customers nyaitu expertise and skills in serving customers, direct visits to clients' homes, and response to customer suggestions and criticisms. For further research is recommended to add another variable to the expanded scope of the study. Keywords: Service Of Quality, Quality Function Deployment, House Of Quality